The Negotiating Game: How To Get What You Want - Chester L. Karrass
This book is designed for anyone interest in reaching their objectives when dealing with others. Whether negotiating in business, politics or love, this book shows you how to tap powerful resources to show readers how to analyze power and improve their strengths, how to make concessions without weakening their position, and how to set goals that reflect their aspirations. By using the author's framework of strategy and tactics, readers learn how to prepare themselves for negotiation as well as recognize, understand and apply traits of effective negotiators. By the author of "Give and Take".